2009
DOI: 10.1126/science.1176450
|View full text |Cite
|
Sign up to set email alerts
|

The Insect Neuropeptide PTTH Activates Receptor Tyrosine Kinase Torso to Initiate Metamorphosis

Abstract: Holometabolous insects undergo complete metamorphosis to become sexually mature adults. Metamorphosis is initiated by brain-derived prothoracicotropic hormone (PTTH), which stimulates the production of the molting hormone ecdysone via an incompletely defined signaling pathway. Here we demonstrate that Torso, a receptor tyrosine kinase that regulates embryonic terminal cell fate in Drosophila, is the PTTH receptor. Trunk, the embryonic Torso ligand, is related to PTTH, and ectopic expression of PTTH in the embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
382
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 325 publications
(427 citation statements)
references
References 20 publications
(32 reference statements)
21
382
1
1
Order By: Relevance
“…On the other hand, sickle↓ and hid↓ (apoptosis effectors) failed to rescue the L3 arrest phenotype. In addition, upregulating the receptor that triggers ecdysone synthesis, Torso, 28 or upregulating the early effectors of ecdysone signaling, Br-C genes, 24 also failed to bypass the deleterious EcR or USP downregulation ( Figure 4b). This is consistent with the lack of ecdysteroid synthesis in experimental larvae shown by direct measurements above (Figure 2b).…”
Section: After Tool Validation (Supplementary Data and Supplementarymentioning
confidence: 99%
“…On the other hand, sickle↓ and hid↓ (apoptosis effectors) failed to rescue the L3 arrest phenotype. In addition, upregulating the receptor that triggers ecdysone synthesis, Torso, 28 or upregulating the early effectors of ecdysone signaling, Br-C genes, 24 also failed to bypass the deleterious EcR or USP downregulation ( Figure 4b). This is consistent with the lack of ecdysteroid synthesis in experimental larvae shown by direct measurements above (Figure 2b).…”
Section: After Tool Validation (Supplementary Data and Supplementarymentioning
confidence: 99%
“…It might be notable here that DHR3 has recently been shown to have an unexpected role as a regulator of cell-autonomous growth through S6 kinase (Montagne et al 2010). Alternatively, in the absence of NOS, PTTH might continue to signal through the Torso/ERK pathway (Rewitz et al 2009), leading to extra endoreplication cycles in the PG cells (Ghosh et al 2010). Double knockdown of various components in the PG-for example, NOS and torso-will help establish the epistatic relationship of these various signaling pathways that contribute to PG size control.…”
Section: No-e75 Interaction-beyond Regulation Of Bftz-f1 Expressionmentioning
confidence: 99%
“…Work over the past decade has indicated that critical size is regulated by at least two signalling pathways; the insulin/IGF-signalling pathway and the PTTH/Ras/Rafsignalling pathway [39,[43][44][45][46][47]. Both appear to control the timing of ecdysteroid synthesis by the prothoraric gland and the cessation of growth: insulin/IGF signalling apparently in response to nutritional status [39,44,45]; PTTH/Ras/Raf signalling in response to temporal information [43,46]; and both insulin/IGF and PTTH/Ras/Raf signalling in response to the developmental status of the growing organs [31,[48][49][50]. However, it is unclear whether these or some other pathway mediates the effects of temperature on critical size.…”
Section: (A) Regulation Of Critical Sizementioning
confidence: 99%